Peace journalism on a shoestring? Conflict reporting in Nigeria's national news media. (March 2021) - Demarest, Leila; Langer, Arnim
Conflicts that occur across ethnic and/or religious identity lines generally have underlying root causes such as economic marginalization and political competition. Yet when these causes are ignored by politicians and the media, and conversely differences in ethnicity and religion are simply propagated as the main conflict causes, this may have serious consequences for people's perceptions concerning the possibility and feasibility of peaceful conflict resolution and coexistence. In this paper, we investigate to what extent Nigerian newspapers practice peace journalism by emphasizing underlying causes of conflict in their reporting rather than stressing ethnic and religious divisions. We make use of a sequential mixed methods approach, which combines a quantitative content analysis of news reports with semi-structured interviews with Nigerian newspaper editors and journalists. Our results indicate that Nigerian newspapers do not explicitly use divisive language when discussing conflicts, but they rarely stress underlying structural causes either. While there is a willingness among Nigerian journalists to avoid potentially escalatory language, a dearth of resources and capacities impedes independent and in-depth analysis concerning the underlying drivers of conflicts.